Studi Arkeologi Historis Makam Pangeran Liting dalam Konteks Marga di Sumatera Selatan - Susidah Ernawati; M. Zalva Zakira; M. Imam Fajri Al-Baroqi; Hudaidah Hudaidah; Risa Marta Yati (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
This study examines the role and influence of Prince Liting in the leadership of the Pegagan Ilir Clan II in the Ogan Ilir region of South Sumatra, and how his legacy of leadership remains alive in the community's collective memory even though the clan system has long been abolished. This study uses a historical approach by exploring primary and secondary sources related to the history of clan governance in South Sumatra. The results show that Prince Liting succeeded in establishing multi-layered legitimacy from both the people, the Dutch colonial government, and the religious community through leadership that combined customary authority with Islamic commitment. His grave in Tanjung Raja now serves as a site of collective memory that goes beyond its usual ceremonial function, reflecting how the local community actively maintains continuity with its historical heritage. The abolition of the clan system in 1983 did not immediately erase the symbolic relevance of its leaders; on the contrary, figures like Prince Liting were further solidified as icons of communal identity. These findings confirm that the historical legitimacy of a local leader is far more enduring than the formal institutions that once protected them.